"Suspended above, and in action": Think aloud as a reflective practice tool - Stephenson, J.; Cronin, C.; Whitehead, A. E. (International Sport Coaching Journal, 2020)
Think Aloud (TA) involves an individual verbalising his or her thoughts throughout the duration of a task. A case study approach examined the experiences of one football coach (Dave) as he engaged in four coaching sessions using TA. Dave completed four reflective diaries, supported by an overall narrative account, TA transcriptions, and two interviews. The aim of the case study was to gain a deeper understanding of Dave`s experiences of using TA in his context. Interpretative phenomenological analysis was utilised and revealed a superordinate theme of "suspended above himself" and actively engaging in the coaching session, which reflects the essence of TA for Dave. This metaphor captures the view that the TA process enabled Dave to move between analysing his own performance as if suspended above himself, and engaging in the action of the coaching session. Five subordinate themes were also generated: improved self-awareness, pedagogy, communication skills, feelings of apprehension, and distraction. These findings provide a rich description of the experience of TA and a novel glimpse into the potential pitfalls associated with TA that will inform coach educators. A further significant contribution is provided by highlighting relevant theoretical considerations that will inform future studies.